Ben Pimlott Memorial Lecture 2018The Women's Suffrage Movement in the Balfour Family. (20th May 2019) - Pedersen, Susan
Abstract: Given on the centenary of women's suffrage, this lecture explores the tensions and conflicts the claim for the vote raised among elite women already enmeshed in parliamentary and political circles. Drawing on the unbuttoned and sometimes angry correspondence among A.J. Balfour's suffragist sisters-in-law Lady Frances Balfour and Lady Betty Balfour, Frances' collaborator (and suffragist leader) Millicent Fawcett, Lady Betty's militant suffragette sister Lady Constance Lytton, and their old friend (and wife of the anti-suffragist Prime Minister) Margot Asquith, it explores the appeal but also the costs of this democratic claim for such "incorporated" women - and explains why some nevertheless supported it.